Unlocking ESP students' views on outcome-based education in marketing skills development: A survey study - Yunita, Sri; Darwis , Riadi; Susilawati (Universitas Negeri Semarang, 2025)
Acquiring professional skills in the ESP class is key to a successful future career. Unfortunately, many students find difficulties in balancing the need for theoretical and practical skills, including the marketing skills for management students. OBE is trusted to provide solutions to balance the students’ intake and practical activities, including marketing skills. This present research aims to shed light on the students’ perceptions of OBE-based ESP courses implemented for marketing skills. A survey method was employed, involving 68 students from the management study program at one private university in Garut, West Java. The results indicated students’ positive perception regarding lecturer support and interaction, active participation in learning, social and critical skills development, assessment and transparency, effectiveness of methods and clarity of learning objectives, planning and motivation for self-study, and learning facilities and resources. However, some areas need to be improved, including discussions or interaction with lecturers, student internal motivation, and accommodating facilities. It is recommended that lecturers and university management work together on these matters to boost students’ potential by developing strategic instructional plans, adequate facilities, an interactive learning environment, and accommodating students’ need for self-study.